2005
DOI: 10.1002/adma.200400963
|View full text |Cite
|
Sign up to set email alerts
|

Water/Methanol‐Soluble Conjugated Copolymer as an Electron‐Transport Layer in Polymer Light‐Emitting Diodes

Abstract: The principal criteria for a polymer-based electron-transport layer (ETL) for use in polymer light-emitting diodes (PLEDs) are the following: 1) the lowest unoccupied molecular orbital (LUMO) of the ETL must be at an energy close to, or even within the p*-band of the emissive semiconducting polymer, and 2) the solvent used for casting the electron-injection material must not dissolve the underlying emissive polymer. Although a few attempts to satisfy these criteria have been reported, [1,2] none have succeeded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
208
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(211 citation statements)
references
References 16 publications
0
208
2
1
Order By: Relevance
“…[1][2][3] In recent years, CPEs have been extensively studied in the field of organic optoelectronics as they can easily form a uniform thin film via solution processing on top of an emissive layer without suffering an intermixing problem between the two layers. [4][5][6][7][8][9][10] It was reported that the charged nature of CPEs has the ability to enhance polymer light-emitting diode (PLED) efficiencies as a consequence of reduction in the energy barrier for electron injection from high work function metals, much in the same way that charge trapping can, but with greater control and no requirement for pre-stressing. 11 This is understood mainly due to the formation of permanent dipoles at the CPE/metal interface 12,13 as also achieved with dipolar self-assembled monolayers (SAMs), but without their need for specific interface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In recent years, CPEs have been extensively studied in the field of organic optoelectronics as they can easily form a uniform thin film via solution processing on top of an emissive layer without suffering an intermixing problem between the two layers. [4][5][6][7][8][9][10] It was reported that the charged nature of CPEs has the ability to enhance polymer light-emitting diode (PLED) efficiencies as a consequence of reduction in the energy barrier for electron injection from high work function metals, much in the same way that charge trapping can, but with greater control and no requirement for pre-stressing. 11 This is understood mainly due to the formation of permanent dipoles at the CPE/metal interface 12,13 as also achieved with dipolar self-assembled monolayers (SAMs), but without their need for specific interface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…However, the water solubility of PFs is difficult to achieve in high concentrations and cosolvents such as methanol are employed to ensure the uniformity of the solutions. 13 Another strategy to assist solubility of π-conjugated polymers is a surfactant layer separating polymer and solvent. The interaction between polymer and surfactant can be due to either hydrophobic-hydrophilic effects 14 or strong physical bonds.…”
Section: Introductionmentioning
confidence: 99%
“…C onjugated polyelectrolytes (CPEs) have attracted significant attention as active materials in polymer optoelectronic devices, [1][2][3][4][5] especially because of their use as effective electron injection/transport layers. [6][7][8][9][10][11][12] A range of CPEs with different counterions (anion/cation) and backbones 13,14 have been synthesized in attempts to understand the role of the ions in the charge injection process.…”
mentioning
confidence: 99%
“…All CPEs reported to date combine charged side chains with mobile counterions such as Na þ , Br -, and tetrasubstituted borates such as BPh 4 -and BIm 4 -, 10,[17][18][19] which can migrate during device operation and lead to long turn-on times and redistribution of the internal field. 16 These mobile ions make the device operation mechanism more complicated, not only because they could alter the work function of the cathode 10,15 but also because ions also have an impact on the luminescence of the light-emitting layer, 20 and they introduce some of the doping characteristics of polymer light-emitting electrochemical cells (PLECs).…”
mentioning
confidence: 99%